Localisation of RFID tags in RFID smart rack - Song, Hong Sheng (2015)
Radio-Frequency Identification (RFID) smart racks system is an extremely useful inventory management application of localization technology based on RFID technology. RFID antennas are mounted on the rack to detect RFID passive tags attached to stuffs placed on the rack. Each item on the rack would be detected with the help of the attached tag. The position and movement of each item would be roughly estimated by analyzing the collected data. This application improves the automation inventory management and has great advantages in retailing, manufacturing, logistics and other fields. This final year project aims to analyse the RFID data set including Received Signal Strength Indication (RSSI) and phase distribution of multi-tier racks in order to determine the location of RFID-tagged objects on the rack. Experiments are carried out on an RFID smart rack testbed to benchmark the impact of features on localisation. The focus of the report is the analysis of RFID data set comprising of ID, timestamp, RSSI, and phase values. The data analysis is accomplished on Excel by interpreting histograms and line charts of RSSI as well as radar charts of phases.